RETRACTION: Lacramioara Serban I, Hogas M, Ciobica A, Dobrin R, Petrariu F. The effects of chronic manganese administration on blood pressure in rats. Arch Biol Sci. 2014;66(1):157-60. DOI:10.2298/ABS1401157L. - Editorial, Journal (Archives of Biological Sciences, 2016)
We are retracting the article Lacramioara SI, Hogas M, Ciobica A, Dobrin R, Petrariu F. The effects of chronic manganese administration on blood pressure in rats. Arch Biol Sci. 2014;66(1):157-60. DOI:10.2298/ABS1401157L as a redundant publication of the article Lacramioara Serban I, Hogas M, Ciobica A. The effects of chronic manganese administration on blood pressure in rats. Arch Biol Sci. 2013;65(3):1195-8. DOI:10.2298/ABS1303195S. The current editorial team cannot establish why this error occurred. We conclude that this is the best step to take in order to correct the literature and alert readers to a redundant article. Link to the retracted article 10.2298/ABS1401157L